1995
DOI: 10.1007/bf00043664
|View full text |Cite
|
Sign up to set email alerts
|

Expression and in vitro targeting of a sunflower oleosin

Abstract: Two distinct cDNAs encoding oleosins (oil body proteins) have been identified by degenerate PCR as transcripts present in the developing seeds of sunflower (Helianthus annuus L. cv. Dwarf Sunbred). One (pSOM) of these is closely related to a reported sunflower oleosin, whilst the other (pSO5) has not been previously described. Different expression patterns were observed for the two cDNAs, pSO5 being expressed earlier than pSOM in seed maturation and oil deposition. The results support the contention that oleos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 20 publications
6
60
1
Order By: Relevance
“…Pathway of Oleosin-Evidence to date suggests that oleosins are integrated into ER membranes co-translationally, following a SRP-and Sec61-dependent pathway (27)(28)(29)34). To place oleosin topology in context, we needed to define the targeting pathway of oleosin into our experimental system of canine pancreatic membrane.…”
Section: Er Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathway of Oleosin-Evidence to date suggests that oleosins are integrated into ER membranes co-translationally, following a SRP-and Sec61-dependent pathway (27)(28)(29)34). To place oleosin topology in context, we needed to define the targeting pathway of oleosin into our experimental system of canine pancreatic membrane.…”
Section: Er Targetingmentioning
confidence: 99%
“…Current evidence suggests that oleosin targets to the ER by an SRP-mediated pathway; oleosin mRNA is found in ERbound polyribosomes (27), and exogenous SRP inhibits oleosin translation in vitro (28). Oleosin expression in yeast mutants also indicates a requirement for SRP and Sec61 (29).…”
mentioning
confidence: 99%
“…Subsequent studies showed that in vitrc-translated oleosin could be targeted to canine pancreatic microsomes but not to erythrocytes, plastids, heat-inactivated canine pancreatic microsomes, or oil bodies (Hills et al, 1993;Loer and Herman, 1993). Although these experiments did not demonstrate the pathway of ER targeting, it has been found that the signal recognition particle is capable of causing translational arrest in vitro (Thoyts et al, 1995). This provides preliminary evidence for a cotranslational, signal recognition particle-mediated targeting pathway but does not rule out post-translational ER targeting of oleosins (Ng et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In developing oilseeds, oleosin is localized on the surface of the oil body, which is the main site of triacylglycerol storage [7]. There is evidence to suggest that oleosin is co-translationally integrated into rough endoplasmic reticulum (rER) membranes [8,9]. It is also known from biochemical experiments that biogenesis of oil bodies parallels the localisation of oleosins in rER membranes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known from biochemical experiments that biogenesis of oil bodies parallels the localisation of oleosins in rER membranes [10,11]. Even though signal sequence for targeting of oleosin to the sites where oil bodies are formed is not known [8,10,12,13] These data indicate that there is dynamic interaction between sites of oil body formation and oleosin synthesis [14,15]. Oleosins are unusual proteins because they possess three different functional domains: a 70-80-residue uninterrupted hydrophobic domain is flanked by relatively polar amino-and carboxy-terminal domains.…”
Section: Introductionmentioning
confidence: 99%